ADVANCING QUALITY IN HIGHER MATHEMATICS CLASSES VIA MATHEMATICAL PROGRAMS - Abdujabbor Abdurazakov; Anvarjon Fozilov (Western European Studies, 2024)
This article presents a comprehensive methodology for improving lesson effectiveness by leveraging mathematical programs to address practical problems, specifically focusing on the management of reserves. Through the application of differential calculus, the study delves into the optimization of storage costs, employing gradient methods to attain optimal solutions. By elucidating the intricacies of total cost calculation, this research underscores the efficacy of mathematical programs in fostering deeper understanding and proficiency in higher mathematics education. Through practical examples and theoretical frameworks, this article elucidates the potential of mathematical programs to elevate the quality of instruction in higher mathematics classes, offering valuable insights for educators and practitioners alike
Keywords: cost; storage; gradient; image